3x+6=10x+3

Simple and best practice solution for 3x+6=10x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6=10x+3 equation:


Simplifying
3x + 6 = 10x + 3

Reorder the terms:
6 + 3x = 10x + 3

Reorder the terms:
6 + 3x = 3 + 10x

Solving
6 + 3x = 3 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
6 + 3x + -10x = 3 + 10x + -10x

Combine like terms: 3x + -10x = -7x
6 + -7x = 3 + 10x + -10x

Combine like terms: 10x + -10x = 0
6 + -7x = 3 + 0
6 + -7x = 3

Add '-6' to each side of the equation.
6 + -6 + -7x = 3 + -6

Combine like terms: 6 + -6 = 0
0 + -7x = 3 + -6
-7x = 3 + -6

Combine like terms: 3 + -6 = -3
-7x = -3

Divide each side by '-7'.
x = 0.4285714286

Simplifying
x = 0.4285714286

See similar equations:

| Hg(x)=2g(x) | | (5x-1)/x=1 | | -40(-28/3) | | .1(f-7)+.05f=.8 | | -(x+3)=2+7 | | log32b=-1/4 | | 42=3w-9 | | 3x+2(3)=4 | | 5-3x=-4[3(x+2)-1] | | 7d=4+6d | | 2(-14/3)-40 | | 9y+4=8y-5 | | -2v/9=-12 | | 8=y/25.6 | | .4(e+5)-.3e=17 | | (5x-1)/1=1 | | 8(4-x)=4(x+5) | | 3x-6.2=14.2 | | -8d=-9d+7 | | 30=-5/2u | | 90=(x+2)(y+1.5) | | 7f/3=5 | | m^2-10m+19=-8 | | 5X+3-X=15+X | | 4c=(a-b)/3 | | 49v^2+16=-56v | | b/3=15.2 | | 10n=7n+9 | | log(132-4x)=2 | | 54=d | | 2x+54=24 | | Cos(5x)=0.8 |

Equations solver categories